Oral health status and salivary IgA concentration and in type 1 diabetic patients - Mustafa, Nazih Shaban; Mustafa Al-Ahmad, Basma Ezzat (2011)
Objective: This study was performed to study the relationship between salivary IgA concentrations in normal individuals, early onset type 1 D.M patients and the oral health status. Also to correlate the salivary IgA concentration with the salivary flow rate, dental caries, gingivitis and age of diabetic patients. Materials and Method: Sixty individuals were included in this study, divided into 2 groups , 1st group 12 normal healthy non-diabetic individuals. while the second group 48 patients is divided into 2 sub groups , 24 each treated by insulin injections and the subgroup early diagnosed patients considered as untreated type 1 group, to monitor salivary IgA concentration, salivary flow rate, and serum glucose level Results & Conclusions: Negative correlations were found between salivary IgA concentration and salivary flow rate and age. Positive correlations were seen with blood glucose concentration, dental caries, and gingivitis. Salivary IgA concentration in the total diabetic groups was higher than the normal non-diabetic group, and the difference was highly significant, while no significant difference was seen in the salivary IgA concentration between the males and the females in both groups. The diabetic patients showed lower salivary flow rate, and more caries and gingivitis than the normal non-diabetic patients.